Meta-analysis of the prevalence of norovirus and hepatitis a virus in berries - Miotti, Camila (2024)
Norovirus (NoV) and hepatitis A virus (HAV) stand as the predominant agents associated with viral foodborne infections. Outbreaks have been documented to be caused by various types of food items, including fresh and/or frozen berries. Comprehensive data concerning crucial viral pathogens in berries remain limited and are not currently available in aggregate form. Consequently, the present study aimed to compile the existing information regarding the prevalence of NoV and HAV in this matrix. Records of foodborne viruses were systematically extracted from database repositories up to December 2022, adhering to PRISMA standards and were subjected to a multilevel random effect meta-analysis model to determine the mean occurrence rate of NoV and HAV. A high heterogeneity across studies was observed (I2 = 82 %), reflecting variations in the prevalence of sampling locations, years, berry types, and sample conditions, among other potential contributing factors. The prevalence of NoV and HAV in berries was calculated at 2.12 % (95 % CI 1.74–2.59 %), and no statistically differences were observed among the viral types or genogroup categories. However, it is important to clarify that this estimate should be taken with caution given the high heterogeneity. There was no discernible correlation between viral prevalence and any particular berry type. However, there was a temporal correlation observed with the year of sampling, revealing a significantly decreasing trend throughout the study period. A significant influence of the sample condition (fresh or frozen) was observed in relation to the prevalence of NoV GII and HAV. Overall higher viral prevalences were identified in berries originating from African countries as compared to those sourced from other continents. It was also noted that the prevalence of NoV GI was significantly higher in samples collected directly from farms compared to those obtained from retailers. The outcomes of this comprehensive meta-analysis propose that while viral contamination of berries is diminishing in more recent times, the prevalence remains substantial in certain African countries, having a significant risk for foodborne infections. It is imperative to implement intervention strategies in these regions to enhance product safety.